2021
DOI: 10.2337/dc20-2398
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Adiposity and Cord Blood C-Peptide as Mediators of the Maternal Metabolic Environment and Childhood Adiposity

Abstract: OBJECTIVE Excessive childhood adiposity is a risk factor for adverse metabolic health. The objective was to investigate associations of newborn body composition and cord C-peptide with childhood anthropometrics and explore whether these newborn measures mediate associations of maternal midpregnancy glucose and BMI with childhood adiposity. RESEARCH DESIGN AND METHODS Data on mother/offspring pairs (N = 4,832) from the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…This is typically ascribed to increased insulin production by the fetal pancreas in response to maternal hyperglycemia, although transplacental insulin passage may contribute (1,39). As noted by others, we observed an independent association between maternal BMI and cord blood insulin which may reflect a role for subclinical insulin resistance in overweight or obese individuals that have not been diagnosed with diabetes (39)(40)(41).…”
Section: Discussionsupporting
confidence: 77%
“…This is typically ascribed to increased insulin production by the fetal pancreas in response to maternal hyperglycemia, although transplacental insulin passage may contribute (1,39). As noted by others, we observed an independent association between maternal BMI and cord blood insulin which may reflect a role for subclinical insulin resistance in overweight or obese individuals that have not been diagnosed with diabetes (39)(40)(41).…”
Section: Discussionsupporting
confidence: 77%
“…A word of caution is necessary when investigating birth weight in the context of gestational obesity as it has been suggested that neonatal adiposity, and not total weight, is independently associated with childhood adiposity [ 71 ]. The association between placental oxidised fatty acids and neonatal outcomes, including adiposity, has never been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in growth trajectories could be explained by sex differences in body composition present at birth and birth weight Z ‐scores, and different magnitudes of absolute gain in fat free mass between boys and girls during the first months of life 24 . It appears that higher levels of neonatal adiposity, as opposed to higher weight, is associated with childhood obesity 25,26 . In the current study, differences in body composition could not be investigated as no anthropometric data, apart from weight and length, were available.…”
Section: Discussionmentioning
confidence: 92%